D-Ribose Interferes with Quorum Sensing to Inhibit Biofilm Formation of Lactobacillus paraplantarum L-ZS9 - Liu, Lei; Wu, Ruiyun; Zhang, Jinlan; Shang, Nan; Li, Pinglan (Frontiers in Microbiology, 2017)
Biofilms help bacteria survive under adverse conditions, and the quorum sensing (QS) system plays an important role in regulating their activities. Quorum sensing inhibitors (QSIs) have great potential to inhibit pathogenic biofilm formation and are considered possible replacements for antibiotics; however, further investigation is required to understand the mechanisms of action of QSIs and to avoid inhibitory effects on beneficial bacteria. Lactobacillus paraplantarum L-ZS9, isolated from fermented sausage, is a bacteriocin-producing bacteria that shows potential to be a probiotic starter. Since exogenous autoinducer-2 (AI-2) promoted biofilm formation of the strain, expression of genes involved in AI-2 production was determined in L. paraplantarum L-ZS9, especially the key gene luxS. d-Ribose was used to inhibit biofilm formation because of its AI-2 inhibitory activity. Twenty-seven differentially expressed proteins were identified by comparative proteomic analysis following d-ribose treatment and were functionally classified into six groups. Real-time quantitative PCR showed that AI-2 had a counteractive effect on transcription of the genes tuf, fba, gap, pgm, nfo, rib and rpoN. Over-expression of the tuf, fba, gap, pgm and rpoN genes promoted biofilm formation of L. paraplantarum L-ZS9, while over-expression of the nfo and rib genes inhibited biofilm formation. In conclusion, d-ribose inhibited biofilm formation of L. paraplantarum L-ZS9 by regulating multiple genes involved in the glycolytic pathway, extracellular DNA degradation and transcription, and translation. This research provides a new mechanism of QSI regulation of biofilm formation of Lactobacillus and offers a valuable reference for QSI application in the future.